2008
DOI: 10.1007/s11099-008-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization effects on leaf morphology and evaluation of leaf area and leaf area index prediction models in sugar beet

Abstract: In a two-year experiment (2002)(2003), five N application rates [0, 60, 120, 180, and 240 kg(N) ha -1 , marked N 0 , N 60 , N 120 , N 180 , and N 240 , respectively] were applied to sugar beet cv. Rizor arranged in a Randomized Complete Block design with six replications. Leaf shape parameters [leaf area (LA), maximum length (L), maximum width (W), average radial (AR), elongation (EL), and shape factor (SF)] were determined using an image analysis system, and leaf area index (LAI) was non-destructively measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Blanco and Folegatti (2005) predicted leaf area by a linear model LA=-4.27 + 0.88 L×W with high accuracy and only little differences observed between the cultivars and environment. Tsialtas and Maslaris (2008) documented that in sugar beet a model developed based on leaf dimensions [LA= 31.928 + 0.5083 L×W] satisfactorily predicted LA better than when the leaf width or length was solely used. Similarly, Lu et al (2004) proposed that the simple and linear relationships between leaf area and leaf dimensions (length and width) might be useful for nondestructive estimation of plants leaf area.…”
Section: Resultsmentioning
confidence: 99%
“…Blanco and Folegatti (2005) predicted leaf area by a linear model LA=-4.27 + 0.88 L×W with high accuracy and only little differences observed between the cultivars and environment. Tsialtas and Maslaris (2008) documented that in sugar beet a model developed based on leaf dimensions [LA= 31.928 + 0.5083 L×W] satisfactorily predicted LA better than when the leaf width or length was solely used. Similarly, Lu et al (2004) proposed that the simple and linear relationships between leaf area and leaf dimensions (length and width) might be useful for nondestructive estimation of plants leaf area.…”
Section: Resultsmentioning
confidence: 99%
“…The most important part of stinging nettle is leaf and leaf area is an important variable in physiological and agronomical researches. As well as plant yield and quality are influenced by photosynthesis and transpiration rate that are intimately linked with leaf area [23]. Therefore recording of leaf area during growth and development can be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…They predicted leaf area by model LA=-4.27 + 0.88 L×W with high accuracy and only little differences between the cultivars, location and growing systems. For leaf area prediction models in sugar beet, the results of study of Tsialtas and Maslaris [23] showed model based on both leaf dimensions [LA= 31.928 + 0.5083 L×W] predicted LA better than that using only leaf width or length. Similar reports from Kumar and Sharma [24], Silva et al [25] and Rouphael et al [26] in leaf area estimation of clary sage (Salvia sclarea L.), potato (Solanum tubersum L.) and rose (Rosa hybrid L.) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation